Integrating Automatic Speech Recognition (ASR) into a Website for EFL Speaking Practice: Needs, Design, and Evaluation - Iwan Fauzi; Dina Mardiana; Orbit Thomas (Journal of English Language Studies, 2026)
This research examines a speech recognition product system, Automatic Speech Recognition (ASR), developed through a research and development (R&D) process based on the ADDIE (analysis, design, development, implementation, and evaluation) model. The prototype resulting from this research was an ASR tool aimed at EFL students practicing English speaking at the intermediate level. Prior to product development, researchers conducted a need analysis to determine whether the prototype would evolve into a necessary learning support tool for spoken English practice. Then, the product's feasibility was tested by reviewing two independent experts from different domains: an ICT (information and communication technology) expert and a TELL (technology-enhanced language learning) expert. To evaluate the ASR system with users, 22 EFL students were purposively recruited for the test. Results indicate that the ASR system serves as a practical application of an educational tool, providing accessibility, usability, and interactive feedback, which encourage users' engagement and language learning. However, a limitation of this study is that speech recognition accuracy, especially for non-native English speakers, remained inconsistent.